Determination of free radical scavenging activities and total phenolic content of basil (Ocimum basilicum L.) - Aburigal, Yasmin A. A.; Mirghani, Mohamed Elwathig Saeed; Elmogtaba, Elfadl Y.; Sirible, Awatif A. M.; Hamza, Nada; Hussein, Ismail H. (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The present study was carried out to determine the antioxidant activity and total phenolic content of Ocimum basilicum collected from different regions of the world. The extraction of plant material have been analysed for their DPPH free radical scavenging activity of six basil accessions and their total phenolic content (TPC). The results suggest that the highest antioxidant activity was found in V4 (from Thailand) and the lowest antioxidant activity was found in V6 (from Maldives). The highest amount of phenolic content was found in V6 (from Maldives) and the lowest phenolic content was found in V4 (from Thailand). This study shows that basil is good sources of free-radical scavenging compounds and has their traditional medicinal application.